Changing Body Representation Through Full Body Ownership Illusions Might Foster Motor Rehabilitation Outcome in Patients With Stroke - Matamala-Gomez, Marta; Malighetti, Clelia; Cipresso, Pietro; Pedroli, Elisa; Realdon, Olivia; Mantovani, Fabrizia; Riva, Giuseppe (Frontiers in Psychology, 2020)
How our brain represents our body through the integration of internal and external sensory information so that we can interact with our surrounding environment has become a matter of interest especially in the field of neurorehabilitation. In this regard, there is an increasing interest in the use of multisensory integration techniques—such as the use of body ownership illusions—to modulate distorted body representations after brain damage. In particular, cross-modal illusions such as mirror visual feedback therapy (MVFT) have been widely used for motor rehabilitation. Despite the effectiveness of the MVFT for motor rehabilitation, there are some limitations to fully modify the distorted internal representation of the paretic limb in patients with stroke. A possible explanation for this relies on the physical limitations of the mirror in reproducing upper limb distortions, which can result in a reduced sense of ownership of the mirrored limb. New digital technologies such as virtual reality and 360º videos allow researchers to create body ownership illusions by adapting virtual bodies so that they represent specific morphological characteristics including upper limb distortions. In this manuscript, we present a new rehabilitation approach that employs full virtual body ownership illusions, using a 360º video system, for the assessment and modulation of the internal representation of the affected upper limb in stroke patients. We suggest modifying the internal representation of the upper limb to a normal position before starting motor rehabilitation training.